Christos J. Paraskevopoulos, Interpreting convergence in the European Union. Patterns of collective action, social learning and Europeanization - Σπανού, Καλλιόπη (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
[Δεν διατίθεται περίληψη / no abstract available]